“DE LO PEQUEÑO A LO GRANDE”: EL PRT-ERP Y LAS ACCIONES ARMADAS CONSIDERADAS COMO CUALITATIVAMENTE MENORES (1971-1976). - IAZZETTA, MARCO (Universidad Nacional del Litoral, 2015)
The PRT-ERP was one of the paradigmatic armed left-wing organizations during the 70’s in Argentina. This paper aims to analyze the repertoire of armed actions developed by the organization during 1971-1976. To achieve this goal, we’ll privilege the study of the operations considered as “qualitatively” inferiors (attacks, executions, propaganda acts, etc.) over the assaults of battalions and others military detachments and the combats deployed by the Mount Company Ramón Rosa Jimenez in Tucuman.